Catholicism and the roots of Nazism : religious identity and National Socialism - Hastings, Derek (Oxford Univ. Press, 2010)
"Derek Hastings illuminates an important and largely overlooked aspect of Nazi history, revealing National Socialism's close, early ties with Catholicism in the years immediately after World War I, when the movement first emerged." "Although an antagonistic relationship between the Catholic Church and Hitler's regime developed later during the Third Reich, the early Nazi movement was born in Munich, a city whose population was overwhelmingly Catholic. Focusing on Munich and the surrounding area, Hastings shows how Catholics played a central and hitherto overlooked role in the Nazi movement before the 1923 Beerhall Putsch. He examines the striking Catholic-oriented appeals and imagery exploited by the movement and reveals how many of the early Nazi movement's leading publicists and propagandists came from the disaffected ranks of local Catholic elites, ranging from members of Catholic university fraternities to influential clergy." "As Hastings shows, the political mobilization of these early Nazi-Catholic activists succeeded largely because they were able to build upon local traditions of radical nationalism, suspicion of ultramontanism, and opposition to political Catholicism that had become increasingly pervasive in Munich before the First World War. In the aftermath of the infamous failure of the November 1923 Beerhall Putsch, however, the movement changed dramatically. Re-founded in early 1925, the Nazi party failed to regain Support in Catholic Munich. Hastings charts how the early Catholic orientation of the Nazi movement was increasingly abandoned and eventually replaced by the highly ritualized, yet distinctly anti-Christian, form of secular-political religion that characterized the Nazis after 1933."--BOOK JACKET.